Energy Transfer to Ni-Amine Complexes in Dual Catalytic, Light-Driven C-N Cross-Coupling Reactions - Kudisch, Max; Lim, Chern-Hooi; Thordarson, Pall; Miyake, Garret M (Journal of the American Chemical Society, 2019)
Dual catalytic light-driven cross-coupling methodologies utilizing a Ni(II) salt with a photocatalyst (PC) have emerged as promising methodologies to forge aryl C-N bonds under mild conditions. The recent discovery that the PC can be omitted and the Ni(II) complex directly photoexcited suggests that the PC may perform energy transfer (EnT) to the Ni(II) complex, a mechanistic possibility that has recently been proposed in other systems across dual Ni photocatalysis. Here, we report the first studies in this field capable of distinguishing EnT from electron transfer (ET), and the results are consistent with Förster-type EnT from the excited state [Ru(bpy) ]Cl PC to Ni-amine complexes. The structure and speciation of Ni-amine complexes that are the proposed EnT acceptors were elucidated by crystallography and spectroscopic binding studies. With the acceptors known, quantitative Förster theory was utilized to predict the ratio of quenching rate constants upon changing the PC, enabling selection of an organic phenoxazine PC that proved to be more effective in catalyzing C-N cross-coupling reactions with a diverse selection of amines and aryl halides.